PERANCANGAN MULTIMEDIA INTERAKTIF PENGENALAN ALAT MUSIK ANGKLUNG BERBASIS ANDROID - I Gede Adi Sudi Anggara; I Kadek Ade Semara Putra; Ngakan Putu Darma Yasa (Tanra: Jurnal Desain Komunikasi Visual Fakultas Seni Dan Desain Universitas Negeri Makassar, 2024)
This research aims to produce learning media in the form of interactive multimedia. This interactive multimedia is filled with learning content needed by early childhood so that it can provide. The learning content that is filled is the introduction of angklung. Angklung is a traditional musical instrument originating from West Java and has been recognized by UNESCO. Various ways can be done to preserve angklung, one of which is by introducing it to young children. The stages that were passed in this research started from collecting data by observation, documentation and literature methods. The development of this media uses software construct 2 which is indeed for making Android-based applications. The resulting interactive multimedia is based on Android which can be played in the form of a mobile phone.